Influence of anisotropic grains (platelets) on the microstructure and uniaxial compressive response of ice-templated sintered alumina scaffolds. (15th February 2017) - Ghosh, Dipankar; Kang, Hyungsuk; Banda, Mahesh; Kamaha, Valere
Abstract: Ice-templated ceramics have unique lamellar pore morphology that offers better compressive mechanical properties in comparison to the typical ceramic foams with isotropic pore morphology. However, for very high-level porosity (>65 vol%) strength difference diminishes. This investigation reveals that by inducing anisotropic grains within the matrix of a fine-grained ceramic, uniaxial compressive response of the ice-templated sintered scaffolds can be markedly enhanced without causing any considerable modification of the total porosity. To address this innovative materials design strategy, we synthesized a series of microstructures by systematically varying the anisotropic grains content in an aqueous suspension and the freezing kinetics to investigate the process-microstructure correlations and understand the structure-property relationships. Microstructural investigations revealed the unique arrangements of the platelets within and out of the lamella walls, where the upward moving ice fronts aligned the platelets' in-plane direction to the ice-growth direction. In the low freezing front velocity regime, platelets were observed to be mainly within the lamella walls, whereas platelets started to develop lamellar bridges with the increasing velocity. As a result, a transition of the pore morphology occurred with the increasing platelets content and the freezing front velocity. A novel method based on the rigorous microstructural analysis is developed to estimate the distribution of the platelets within and out of the walls and the variation of the platelets distribution with the composition and freezing front velocity. A drastic improvement of the compressive mechanical properties (stiffness, strength, energy absorption capacity) was measured due to the platelets' addition, which has been related to the platelets' distribution within and out of the walls and the pore morphology modifications. Results are rationalized based on the role of the platelets during the compressive deformation. Graphical abstract: Image 1